Workshop Pengembangan Kompetensi Mahasiswa Pada Implementasi Teknik Peramalan Kuantitatif Berbasis Software POM QM For Windows - Junianto, Dwi; Suseno, Pangki; Mahariani, Yeni Roha; Wibowo, Bayu Sandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2024)
Business competitiveness today is influenced by factors both internally and externally. For this reason, an effective and efficient operation and production strategy is required. These activities require demand estimation to be one of the keys in production planning and control. This means that forecasting will drive business decisions on the importance of quickly and accurately capturing information about demand. The output of the forecasting value can be the basis of production, capacity, and scheduling systems, financial planning, marketing and labor. Thus, the implementation of a forecasting method that is suitable for the data pattern and the level of accuracy or accuracy becomes an important instrument.